Effects of modified external ventricular drainage vs. an Ommaya reservoir in the management of hydrocephalus with intracranial infection in pediatric patients - Chen, Liuyin; He, Mingzhe; Shi, Lei; Yue, Yanke; Luo, Pengyuan; Fang, Jiangshun; Wang, Na; Cheng, Zhenghai; Qu, Yi; Yang, Zhiguo; Sun, Yaning (Frontiers in Neurology, 2024)
Background Hydrocephalus with intracranial infection (HII) may cause pathological changes in brain tissue structure and irreversible damage to the nervous system. However, intracranial infection is a contraindication to ventriculo-peritoneal (VP) shunt surgery, and the prognosis is improved by early infection control and intracranial pressure reduction. This study evaluated the safety and efficacy of the Ommaya reservoir vs. modified external ventricular drainage (M-EVD) in the management of HII in pediatric patients. Methods This retrospective controlled study included 45 pediatric patients with HII treated with an Ommaya reservoir (n = 24) or M-EVD (n = 21) between January 2018 and December 2022. Clinical outcomes, cerebrospinal fluid (CSF) test results, complications, and outcomes were compared between the Ommaya reservoir and M-EVD groups. Results No patient died during the follow-up period. The two groups were similar regarding age, sex, admission temperature, weight, preoperative serum protein and albumin concentrations, CSF analysis (white blood cell count, glucose concentration, and protein content), and clinical symptoms (P > 0.05). Both groups had significant changes in the CSF test results postoperatively compared with preoperatively (P < 0.05). In the M-EVD group, the median days for 13 children to remove the external drainage tube and receive VP shunt was 19 days. The longest drainage tube retention time was 61 days, and there was no intracranial infection or serious complication related to the drainage tube. After the placement of the Ommaya, the median time required for CSF to return to normal was 21 days, and a total of 15 patients underwent VP shunt surgery. Conclusion The Ommaya reservoir and M-EVD are safe and effective for pediatric patients with HII. Both methods reduce the intracranial pressure and alleviate the symptoms of hydrocephalus, although there are differences between the two methods.